A intervenção fonoaudiológica em crianças com entraves estruturais na constituição psíquica - Mori, Juliana de Souza Moraes (2024)
Supported by the formulation proposed by Cláudia De Lemos (2002) that language acquisition and psychic constitution are solidary processes, this thesis proposes that the logical moment in which the child finds himself and the singularity of his relationship with language be taken into account in the direction of treatment and speech therapy clinical management. With this vector, it proposes that interventions in children with structural obstacles in their psychic constitution and language acquisition should be carried out by listening to fragments arising from sensory, vocal, bodily and even verbal manifestations, considering the character outside the meaning and playfulness of Lalangue – an essential substrate that is found in the initial moments of a child’s linguistic journey and that supports the structuring of the subject in language. It is recognized that such interventions are similar to children's sound games, also known as resonance games and vocalization games, mainly because they are not restricted by the logic of meaning, but rather because they are governed by a dynamic of affections and provided with playfulness. According to Porge (2014) and Pommier (2007), such games are of crucial importance for the subject's inscription in language. Guided by a qualitative approach, through clinical fragments, in light of the theorizing of Cláudia de Lemos (regarding language acquisition) and Lacanian theory (regarding the conception of subject and lalangue), such defense makes it possible to rethink clinical management in the treatment of subjects with initial obstacles in structuring themselves as speakers and in their psychic constitution